Sosialisasi Hands Only CPR (HOCPR) Pada Pengunjung Car Free day (CFD) Samota, Sumbawa, Nusa Tenggara Barat - Hendri Purwadi; Ni Wayan Sri Laksmi; Meri Afridayani (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The incidence of out-of-hospital cardiac arrest increased (OHCA) significantly. The survival rates of OHCA would be decreased 7-10% every minutes. Therefore, the patients with OHCA must be performed cardiopulmonary resuscitation (CPR) immediately. However, CPR is commonly not performed due to lack of knowledge, skills and fair of being transmitted of diseases. Hands Only CPR (HOCPR) is designed for lay rescuer through two simple steps, firstly call the nearest health center, secondly performed compression to the middle of chest. This socialization aimed to improve knowledge and willingness of lay rescuer to perform HOCPR. This socialization has been done in CFD Samota Sumbawa on 18th June 2023. More than 100 flayers have been distributed followed by discussion regarding the importance of CPR. The result of the outreach showed that visitor of CFD Samota were very enthusiastic and they were able and willing to perform HOCPR. Therefore, health care centers, such as hospitals, university and organizations related to emergency sector need to actively provide outreach and demonstrations related to HOCPR.